A new species of Trichoglossum (Geoglossales, Ascomycota) from South Korea - Lee, Seung-Hak; Ko, Pyeung-Yeul; Koh, Ki-Beom; Jun, Yong-Woo; Kim, Young-Jin; Jung, Yong-Hwan; Yoon, Weon-Jong; Oh, Dae-Ju (Phytotaxa, 2021)
Herein, a new species of the genus Trichoglossum is described. The new species named as T. jejuense was collected from Jeju Island in Korea. It is distinguished from other Trichoglossum species by thick, 8-spored asci and 15–16 septate ascospores. Phylogenetic analyses of the internal transcribed spacer of ribosomal RNA and morphological characteristics suggest that T. jejuense is a distinct species.